Factors influencing the quality of grassroots trade union presidents in Vietnamese private enterprises - Hung, Le Manh; Anh, Vu Thi Kim; Huong, Tran Thi (Universitas Muhammadiyah Yogyakarta, 2025)
Amidst Vietnam’s rapid economic growth and deepening international integration, the private sector has emerged as a vital engine for development. This dynamism, however, presents complex labor relations challenges, highlighting the effectiveness of grassroots trade unions under the spotlight. The quality of Grassroots Trade Union Presidents (GTUPs) is paramount in mediating these relations and ensuring workers' rights, yet the determinants of their effectiveness remain underexplored. This study addresses this critical gap by systematically analyzing the factors influencing GTUP quality. Drawing on quantitative data from a comprehensive survey of 393 trade union officials in Vietnamese private enterprises, the study proposes and tests a framework comprising four influential domains: trade union organization, enterprise characteristics, socio-economic context, and demographic attributes. The findings confirm that all four domains significantly shape GTUP quality. Critically, factors internal to the workplace—namely trade union organization and the enterprise environment—emerge as the most potent predictors of leadership effectiveness. Furthermore, an ANOVA analysis reveals significant variations in GTUP quality across different industry sectors and enterprise sizes, underscoring the inadequacy of a 'one-size-fits-all' approach to leadership development. This study provides crucial empirical evidence for policymakers and stakeholders. It calls for integrated solutions, including targeted training programs, competitive remuneration policies, and a strengthened legal framework. Enhancing the capacity of GTUPs is not merely an internal union affair but a strategic imperative for fostering harmonious labor relations, improving enterprise productivity, and contributing to the sustainable development of Vietnam's private sector.